People's Republic of China Financial Sector Assessment Program : IOSCO Objectives and Principles for Securities Regulation - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
This is an initial report of the International Organization of Securities Commissions (IOSCO) assessment performed in 2010 as part of the financial sector assessment program (FSAP) of China. The assessment was prepared on the basis of a self-assessment prepared by the China Securities Regulatory Commission (CSRC), public information contained on the CSRC website and the websites of other entities in China, and a review of relevant Chinese laws and regulations. The timely completion of this assessment was greatly facilitated by the cooperation provided by numerous members of the staff of the CSRC. The CSRC has broad regulatory authority over the stock and futures exchanges, the China Securities Depository and Clearing Corporation Limited (SD and C) and other clearing and settlement institutions, securities companies, futures companies, and collective investment scheme (CIS) operators. This paper is divided into two parts. The first part gives summary, key findings, and recommendations. It is further divided into following six parts: (i) introduction; (ii) information and methodology used for assessment; (iii) institutional and market structure- overview; (iv) preconditions for effective securities regulation; (v) key findings; and (vi) recommended action plan and authorities' response. The second part gives tabular detailed assessment.